1999
DOI: 10.1099/00207713-49-1-103
|View full text |Cite
|
Sign up to set email alerts
|

Haloanaerobacter salinarius sp. nov., a novel halophilic fermentative bacterium that reduces glycine-betaine to trimethylamine with hydrogen or serine as electron donors; emendation of the genus Haloanaerobacter

Abstract: A novel halophilic fermentative bacterium has been isolated from the black sediment below a gypsum crust and a microbial m a t in hypersaline ponds of Mediterranean salterns. Morphologically, physiologically and genetically this organism belongs to the genus Haloanaerobacter. Haloanaerobacter strain SG 3903T (T = type strain) is composed of non-sporulating long flexible rods with peritrichous flagella, able to grow in the salinity range of 5-30% NaCI, with an optimum a t 14-15%. The strain grows by fermenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…In hypersaline environments, betaine is a common osmoregulatory compound synthesized at high concentrations by certain halophilic bacteria (42). Betaine can be fermented to yield acetate and trimethylamine by a variety of fermentative bacteria, including halophilic acetogens and other halophiles (19,37,53). Specifically, it has been demonstrated that a methanogen fermenter coculture of Methanohalophilus sp.…”
Section: Discussionmentioning
confidence: 99%
“…In hypersaline environments, betaine is a common osmoregulatory compound synthesized at high concentrations by certain halophilic bacteria (42). Betaine can be fermented to yield acetate and trimethylamine by a variety of fermentative bacteria, including halophilic acetogens and other halophiles (19,37,53). Specifically, it has been demonstrated that a methanogen fermenter coculture of Methanohalophilus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Firmicutes of the Halanaerobiales are abundant in hypersaline environments, including the Great Salt Lake, the Dead Sea, oil wells, saltern ponds in France and California, and a variety of other locations (40,47,57,58,76). Known members are obligately anaerobic, moderately halophilic organisms that gain energy by fermentation of various organic compounds.…”
Section: Vol 71 2005 Phylogeny Of An Endoevaporitic Microbial Commumentioning
confidence: 99%
“…However, the transient formation of similar amounts of trimethylamine (TMA) and acetate indicates that the reduction of betaine, as found in members of the genera Clostridium and Halanaerobacter (9,10), is the first step in degradation. While acetate is utilized mainly by sulfate reducers, trimethylamine is a well-known noncompetitive substrate for methanogens (8,11), allowing them to thrive within the sulfate reduction zone.…”
mentioning
confidence: 99%